2022
DOI: 10.1111/bcp.15411
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptor blockers (ARBs) and manufacturing contamination: A retrospective National Register Study into suspected associated adverse drug reactions

Abstract: The aim of this study was to determine if any suspected adverse drug reactions (ADRs) observed with the use of angiotensin II receptor blockers (ARBs) could be linked to either (a) their unique respective physicochemical and pharmacological profiles and (b) the recently disclosed suspected carcinogenic manufacturing contaminants found in certain sartan drug class batches. Methods:The pharmacology profiles of ARBs were data-mined from the Chemical Database of bioactive molecules with drug-like properties, Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…In contrast, there was no evidence that the risks of all-cause and cardiovascular deaths were increased and after emergent banning. Although NDMA-contaminated valsartan is no longer on the market, the issue of impurities in antihypertensive drugs continues, including recent azide (azidomethyl-biphenyl-tetrazole) issue associated with the angiotensin type 1 receptor antagonist class, namely “sartan’, 12 and the results of this study can offer valuable evidence for determining future health policy stance.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, there was no evidence that the risks of all-cause and cardiovascular deaths were increased and after emergent banning. Although NDMA-contaminated valsartan is no longer on the market, the issue of impurities in antihypertensive drugs continues, including recent azide (azidomethyl-biphenyl-tetrazole) issue associated with the angiotensin type 1 receptor antagonist class, namely “sartan’, 12 and the results of this study can offer valuable evidence for determining future health policy stance.…”
Section: Discussionmentioning
confidence: 91%
“…The O-sulfation of ketoximes (Chart 2) all showed good to excellent conversions as measured by 1 H NMR spectroscopy and isolated yields (typically 67-98%) after an extractive purification protocol (Supplementary materials). These results also showed that mono-substituted aromatic oximes were not influenced by the attached groups from highly electron-donating methoxy groups (2e) to highly electron-withdrawing nitro groups (2f).…”
Section: Resultsmentioning
confidence: 99%
“…The amide functional group is one of the most important and widely encountered structural units in organic chemistry and biochemistry. The amide bond is commonly found in bioactive drug molecules including valsartan, an angiotensin receptor blocker (ARB) [1]; sitagliptin, an anti-diabetic medicine used to treat type-2 diabetes [2]; olaparib, a PARP inhibitor used to treat BRCA-mutated advanced ovarian cancer [3]; and apixaban, an anti-coagulant used to prevent stroke in nonvalvular atrial fibrillation via the inhibition of Factor Xa (Figure 1) [4].…”
Section: Introductionmentioning
confidence: 99%
“…risk and carcinogenic contaminant during valsartan prescription have been reported (11), but there was little safety information available at the time of this study in Japan. This study aimed to elucidate the prescribing patterns and cumulative dose per patient of valsartan-containing drugs to provide information related to the assessment of patient health effects caused by NDMA.…”
Section: Study 2: Drug Utilization Study Of Valsartan-containing Drug...mentioning
confidence: 99%